2020
DOI: 10.1186/s12302-020-00327-4
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene microplastics do not affect juvenile brown trout (Salmo trutta f. fario) or modulate effects of the pesticide methiocarb

Abstract: Background: There has been a rising interest within the scientific community and the public about the environmental risk related to the abundance of microplastics in aquatic environments. Up to now, however, scientific knowledge in this context has been scarce and insufficient for a reliable risk assessment. To remedy this scarcity of data, we investigated possible adverse effects of polystyrene particles (10 4 particles/L) and the pesticide methiocarb (1 mg/L) in juvenile brown trout (Salmo trutta f. fario) b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 70 publications
1
8
1
Order By: Relevance
“…PS MP did neither affect the AChE activity nor the activity of two CbEs of brown trout. Similar results were found for juvenile brown trout exposed to the same PS MP (10 4 particles/L) for 96 h [86]. Furthermore, PS MP (45 µm) did not cause alterations in the activity of AChE in zebrafish [29].…”
Section: Effects Of Mpsupporting
confidence: 83%
See 2 more Smart Citations
“…PS MP did neither affect the AChE activity nor the activity of two CbEs of brown trout. Similar results were found for juvenile brown trout exposed to the same PS MP (10 4 particles/L) for 96 h [86]. Furthermore, PS MP (45 µm) did not cause alterations in the activity of AChE in zebrafish [29].…”
Section: Effects Of Mpsupporting
confidence: 83%
“…Nevertheless, the data basis of the chemical analytic seems to be too limited to draw clear conclusions about the sorption of amitriptyline to MP. Only few studies found, like the present study, no interaction between MP and pollutants [86,90]. However, it cannot be excluded that this might have been resulting from a bias against the publication of negative results [27].…”
Section: Co-exposure Of Mp and Amitriptylinecontrasting
confidence: 67%
See 1 more Smart Citation
“…Nonetheless, the role of MPs as vectors of contaminants still presents contradictory interpretations [124,125]: while some ecotoxicological studies have determined that plastic can have a synergic effect with respect to pollutants (e.g., [120,126,127]), other studies have reported negligible changes in contaminant uptake in the presence of MPs (e.g., [128][129][130]).…”
Section: Interaction Of Mps With Micropollutantsmentioning
confidence: 99%
“…Yin et al (2019) found that microplastic exposure altered behavioural traits, energy reserves and the nutritional quality of demersal black rockfish. However, some studies have concluded that microplastics have no effect on organisms, unless associated with organic contaminants (Le Bihanic et al, 2020; Schmieg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%